2014
DOI: 10.1089/ten.tea.2013.0553
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of TAK1 and/or JAK Can Rescue Impaired Chondrogenic Differentiation of Human Mesenchymal Stem Cells in Osteoarthritis-Like Conditions

Abstract: Objective: To rescue chondrogenic differentiation of human mesenchymal stem cells (hMSCs) in osteoarthritic conditions by inhibition of protein kinases. Methods: hMSCs were cultured in pellets. During early chondrogenic differentiation, these were exposed to osteoarthritic synovium-conditioned medium (OAS-CM), combined with the Janus kinase ( JAK)-inhibitor tofacitinib and/or the transforming growth factor b-activated kinase 1 (TAK1)-inhibitor oxozeaenol. To evaluate effects on chondrogenesis, the glycosaminog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 41 publications
1
24
0
Order By: Relevance
“…Randeau et al observed comparable levels of proteoglycan production and gene expression of COL1, COL2 and COL10 between chondrogenically differentiating MSCs cultured in alginate beads and pellets. In previous studies we have used pellet cultures to investigate the effect of SCM 47,48 , and have confirmed that the effect on COL2 and ACAN gene expression is similar in alginate and pellet cultures. Furthermore, MSCs in alginate have formed cartilage matrix in vivo 49,50 .…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Randeau et al observed comparable levels of proteoglycan production and gene expression of COL1, COL2 and COL10 between chondrogenically differentiating MSCs cultured in alginate beads and pellets. In previous studies we have used pellet cultures to investigate the effect of SCM 47,48 , and have confirmed that the effect on COL2 and ACAN gene expression is similar in alginate and pellet cultures. Furthermore, MSCs in alginate have formed cartilage matrix in vivo 49,50 .…”
Section: Discussionmentioning
confidence: 55%
“…However, each experiment demonstrated a clear inhibitory effect. Moreover, in previous experiments we observed a strong negative effect of OA-SCM, pooled from seven donors, on the chondrogenic differentiation of different MSC donors in pellet culture 47,48 . Given that the negative impact of SCM on MSC chondrogenesis is consistent, we believe that the use of one MSC donor per experiment is sufficient.…”
Section: Discussionmentioning
confidence: 80%
“…After 24 hours after isolation, explants were stimulated with hrIL-β1 (1 ng/ml) (R&D Systems, Minneapolis, MN, USA) or with osteoarthritic synovium-conditioned medium OAS-CM 10 % (v/v) [ 16 ]). Following 24 hours of culture in proinflammatory conditions (48 hours after explant isolation), explants were randomly assigned to compression groups with corresponding unloaded controls.…”
Section: Methodsmentioning
confidence: 99%
“…Samples were centrifuged for 10 min at 13,000 rpm and supernatant was transferred to fresh tubes. Sulfated GAG measurements were done using the dimethylmethylene blue assay as previously described [19]. DNA content was determined using the Picogreen dsDNA assay kit (Quant-it) according to manufacturer's instructions.…”
Section: Quantification Of Sulfated Gag and Dna Contentmentioning
confidence: 99%